2019
DOI: 10.3390/polym11020196
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Structures, and Magnetic Properties of a Series of Heterotri-, Tetra- and Pentanuclear LnIII–CoII Compounds

Abstract: Three types of Ln(III)–Co(II) heterometallic compounds, LnCo2(L1)7(bipy)2 (Ln = Pr-1, Eu-2, Sm-3, Gd-4, Tb-5, Dy-6) (L1 = 4-chlorobenzoate, bipy = 2,2′-bipyridine), Ln2Co2(L2)10(bipy)2 (Ln = Sm-7, Gd-8, Tb-9, Dy-10, Ho-11, Er-12, Yb-13), (L2 = 2,4-dichlorobenzoate, bipy = 2,2′-bipyridine, phen = 1,10-phenanthroline), and Ln2Co3(L1)12(bipy)2 (Ln = Ho-14, Er-15, Yb-16), were synthesized under hydrothermal conditions and characterized by single crystal X-ray diffraction, IR spectroscopy and magnetic measurements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…The fitting of the experimental data to the Hamiltonian equation H = −2J(Ŝ Co1ŜGd + S Co2ŜGd )−2J'(Ŝ Co1ŜCo2 ) + DŜ z 2 + Σ i µg e f f → HŜ i , in the whole temperature range, provided the coupling values between Co II -Co II ions (J = +1.3 cm −1 ) and Co II -Gd III ions (J = +0.09 cm −1 ), respectively, with a mean g value of 2.35. This magnetic coupling is in agreement with previous studies in Co II -Gd III complexes, which always present a ferromagnetic coupling when the Co II is a high spin cation [49,50].…”
Section: Magnetism Studiessupporting
confidence: 93%
“…The fitting of the experimental data to the Hamiltonian equation H = −2J(Ŝ Co1ŜGd + S Co2ŜGd )−2J'(Ŝ Co1ŜCo2 ) + DŜ z 2 + Σ i µg e f f → HŜ i , in the whole temperature range, provided the coupling values between Co II -Co II ions (J = +1.3 cm −1 ) and Co II -Gd III ions (J = +0.09 cm −1 ), respectively, with a mean g value of 2.35. This magnetic coupling is in agreement with previous studies in Co II -Gd III complexes, which always present a ferromagnetic coupling when the Co II is a high spin cation [49,50].…”
Section: Magnetism Studiessupporting
confidence: 93%
“…The obtained results 1, 2 are consistent with the other empirical studies on 3d-4f complexes. According to research, the 3d-LnIII exchange interaction is usually ferromagnetic in the case of heavy lanthanides [34][35][36][37][38][46][47][48][49]. The results are also in a good agreement with Kahn et al's theoretical model, which suggested that for the light lanthanide ions(III) with a 4f 1 -4f 6 configuration, the angular and spin moments were antiparallel in the 2S+1 L J free-ion ground state (J = L − S).…”
Section: Magnetic Propertiessupporting
confidence: 63%
“…The 3d2Ln III 2 subunits are then bridged by azide ions [33]. According to the literature [34][35][36][37][38], significant efforts have been made in recent years to construct 3d-4f compounds to obtain novel single-molecule magnets (SMMs). Lanthanide ions, especially Tb III , Dy III , Ho III , and Er III , are widely used in the synthesis of 3d-4f SMMs due to their large In the reported 3d-Ln III complexes there are examples of hetero-di- [24][25][26][27], tri- [28][29][30], tetra- [27,31,32], and octanuclear [33] compounds (Figure 3).…”
Section: Introductionmentioning
confidence: 99%
“…Some enzymes or catalysts in biological reactions are built from zinc complexes [6,7]. Transition metal-polycarboxylate complexes have fascinating magnetic, biological and structural characteristics [8][9][10][11]. The applications of the transition metal complexes of methylenebis(hydroxybenzoic acid) in catalysis, bioinorganic, electrochemistry, corrosion, metallic deactivators, environmental chemistry and separation methods are noteworthy [5,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%